Business Longevity and Islamic Spiritual Values of Micro Business Actors in Klaten Regency Indonesia - Winarno Heru Murjito; Jarot Prasetyo; Purwo Haryono (Cita Konsultindo Research Center, 2024)
The research design uses quantitative survey research. The sampling technique for respondents was carried out by purposive sampling of the community as the respondents are micro business actors in the Klaten area, totaling 110 respondents. By testing the Structural Equation model, researchers tested the relationship between variables in the model simultaneously. Model tests include respondent description test and variable descriptions, item validity test, item reliability test, regression test and moderating test simultaneously using AMOS software tools. The test results prove that there is a direct influence of attitude values, self-efficacy and Cognitive Dissonance on Business Longevity. The moderating test for the Islamic Spiritual Value variable is able to strengthen the three independent variables on the dependent variable. Managerial implications through the proven model require a strategy for stakeholders to develop efforts to increase the Islamic spiritual value ethos. Research findings: the Klaten Regency area has a high level of religiosity, Islamic spiritual values ​​are able to act as a moderating variable